GRAPHITE: A graphical environment for scalable in situ video tracking of moving insects. Issue 4 (26th December 2017) - Rossetti, Blair J.; Dynes, Travis; Brosi, Berry; de Roode, Jacobus C.; Kong, Jun
Abstract: Methods for measuring animal movement are critical for understanding numerous ecological and evolutionary processes. However, few methods are available for small organisms, and even fewer methods offer consistent individual‐level resolution while remaining affordable, scalable and operable in the field. We describe a low‐cost animal movement tracking method with a user‐friendly graphical interface, called GRAPHITE. Our automated software can quantify motions of insects by offline video analysis of inexpensive and lightweight human‐readable tags attached to individual insects. The integrated graphical editor provides a full‐featured environment for users to review the generated tracking data and make individual‐ or group‐level edits. GRAPHITE is a novel video analysis and graphical editing software (Matlab v.9.0.0+) that identifies tags in image frames with a minimal false negative rate, links sequences of corresponding tags into "tracks" for each individual insect, infers the tag identifier, and provides a user‐friendly graphical environment for editing tracking data. Users can either batch process raw video data using the full analysis pipeline or execute GRAPHITE modules independently for a tailored analysis. We demonstrate the efficacy of the developed software with a specific application to the movement of honey bees at the entrance of hives. However, this system can be easily modified to track individually marked insects of 3 mm and larger. A notable advantage of this method is its ability to provide easy access to individual‐level tracking data using human‐readable tags.